Can mental health related hospital visits be relied upon for suicide prevention? - Boctor, Kerstina; Harder, Douglas; Letwiniuk, Liz; Marcoux, Gene; Langhorst, Kristi; Inch, Roxanne; Lapointe, Candace; Balbuena, Lloyd (International Journal of Population Data Science, 2018)
Introduction Even among people with mental disorders, relatively few die of suicide. However, a large proportion of people dying from suicide have seen a physician in the year before death. This raises the question whether focusing on hospital visits for suicide-related outcomes is a viable suicide prevention strategy. Objectives and Approach Our objective was to examine whether a hospital visit for a mental disorder or prior suicide attempt preceded suicide death. We requested Saskatchewan’s provincial coroner for records of people dying of suicide in the Saskatoon Health Region catchment area for the years 2012 to 2016. The coroner’s list was linked with hospital and community mental health databases. Patient charts and medical abstracts in both settings were reviewed for risk factors. Results There were 143 suicide deaths in the time period and the yearly incidence was higher in Saskatoon as compared with the national average. Only 38 percent were seen previously in any Saskatoon hospital for a mental disorder (11 percent for a self-harm diagnosis). The chart review confirmed several known psychological and social risk factors. Having a history of depression or psychosis and alcohol and/or drug use were common. Many decedents also had disadvantaged socio-economic backgrounds characterized by vulnerable housing and being on social assistance. Conclusion/Implications With only 38 percent of decedents being seen in hospital, community-based mental health care and data are important for suicide prevention. Suicide prevention efforts can be aided by facilitating the linkage of community and medical records to better track patients as they move between care settings.